2010
DOI: 10.1177/0891243210374600
|View full text |Cite
|
Sign up to set email alerts
|

Working-Class Job Loss, Gender, and the Negotiation of Household Labor

Abstract: Scholars see the gendered division of household labor as a stronghold of gender inequality.We explore changes in household labor and gender relations when conservative, workingclass families experience employment disruptions. Using data from 49 qualitative interviews conducted with men and women following the forced unemployment of breadwinning husbands, we observe some change in gendered household labor but conclude that a significant degendering of housework is thwarted by institutional-, interactive-, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 48 publications
6
103
1
Order By: Relevance
“…At the same time, more families have adopted a more egalitarian division of household labor (Bianchi, Robinson, & Milkie, 2007) and that may prepare some families for a nontraditional arrangement such as having an SAHF. However, the persistence of family responsibilities and norms of masculinity (Bianchi, Sayer, Milkie, & Robinson, 2012;Bittman, England, Sayer, Folbre, & Matheson, 2003;Brines, 1994;Greenstein, 2000;Legerski & Cornwall, 2010;Tichenor, 1999Tichenor, , 2005 suggest that the shift in work and care arrangements is likely to face opposition that would require a significant difference in earnings between wives and husbands to "push" families into an SAHF work and care arrangement.…”
Section: Exchange Theory Gendered Expectations and Changing Norms Omentioning
confidence: 99%
“…At the same time, more families have adopted a more egalitarian division of household labor (Bianchi, Robinson, & Milkie, 2007) and that may prepare some families for a nontraditional arrangement such as having an SAHF. However, the persistence of family responsibilities and norms of masculinity (Bianchi, Sayer, Milkie, & Robinson, 2012;Bittman, England, Sayer, Folbre, & Matheson, 2003;Brines, 1994;Greenstein, 2000;Legerski & Cornwall, 2010;Tichenor, 1999Tichenor, , 2005 suggest that the shift in work and care arrangements is likely to face opposition that would require a significant difference in earnings between wives and husbands to "push" families into an SAHF work and care arrangement.…”
Section: Exchange Theory Gendered Expectations and Changing Norms Omentioning
confidence: 99%
“…Historically, this has meant that men have been able to mobilize their greater resources to prioritize their careers, including relocating the family for job opportunities (Baldridge, Eddleston, & Veiga, 2006;Bielby & Bielby, 1992;Hardill, Green, Dudleston, & Owen, 1997;Shauman & Noonan, 2006; but see Pixley, 2008). The recent recession provides a unique researchable moment, as more women are likely to be in positions of power vis-à-vis earnings (Legerski & Cornwall, 2010;Mattingly & Smith, 2010). As such, married individuals of various races and classes may now make different determinations about which spouse's career to prioritize and whether it would be logical to relocate their family for new employment opportunities.…”
Section: Introductionmentioning
confidence: 96%
“…Even where women do not have the same earning power as their partners, evidence suggests that the money they earn is vital to the economic survival of the household (Harkness et al, 1997). Despite this shift in the relative importance of men's and women's financial contributions to the household, research has consistently found that traditional ideologies of gendered labour persist (Forret et al, 2010;Legerski and Cornwall, 2010). Women's roles may have changed substantially to include both family and work but working women tend to experience this as a 'stalled revolution' where men's roles have changed relatively little, leaving women bearing the brunt of the additional work required to service family and job commitments (Hochschild, 2003).…”
Section: Introductionmentioning
confidence: 99%